Effect of radiofrequency induced accelerated ageing on physico-chemical, cooking, pasting and textural properties of rice. (March 2021) - Hussain, Syed Zameer; Iftikhar, Farheena; Naseer, Bazila; Altaf, Uzma; Reshi, Monica; Nidoni, Uday Kumar
Abstract: Radiofrequency (RF) heating was explored to induce accelerated ageing in rice to reduce the time of ageing. RF exposure time and moisture content of rice were set at five levels between 10 and 115 min and 9.5–18.5% respectively using central composite rotatable design. The values of different quality attributes of rice viz., volume expansion ratio (VER), water uptake (WU), gel consistency (GC), adhesiveness (ADH), cohesiveness (COH), amylose content (AC), reducing sugars (RS), free fatty acids (FFA), peak viscosity (PV), final viscosity (FV), and overall acceptability varied between 3.79 and 3.88, 269-281 g/100 g, 80–82 mm, (−) 0.35 - (−)1.12 N, 98.45–119.13, 19.22–19.95%, 0.17–0.21%, 1.9–3.4%, 290.35–349.59 RVU, 260.51–290.45 RVU, and 3–4.8 respectively. Models obtained for all the above quality parameters were highly significant (p ≤ 0.0006). RF treated rice differed significantly in various physico-chemical, cooking, textural and pasting properties as compared to fresh rice. WU, GC, FFA, COH, PV and FV increased significantly (p < 0.05), whereas VER, AC and ADH decreased in RF treated rice in comparison to fresh rice. OA of RF treated rice was also significantly (p < 0.05) higher than freshly harvested rice. Design expert predicted 26.25 min of RF exposure time at 16.25% moisture content of rice as optimum condition to induce accelerated ageing in rice. The inference drawn was that the radiofrequency heating can emerge as new approach to accelerate ageing in rice. Highlights: Accelerated ageing is so far restricted to conventional and microwave heating methods. RF heating induced desirable quality changes in rice in a shortest period of time. Highly significant models predicted the qualities attributes of RF treated rice. Optimum condition were 26.25 min of RF exposure time at 16.25% moisture content. RF heating can emerge as a new approach to accelerate ageing in rice.